Sosialisasi Penerapan Pola Hidup Bersih dan Sehat (PHBS) Pada Anak Usia Dini di PAUD - Muhamad Yusup Rachmat; Zulfa Zahira Sufiati (PT. ALHAFI BERKAH INDONESIA, 2024)
Community Service by Students (PMM) is a real form of implementation of higher education values ​​to contribute to society. PMM Group 45 Wave 3 of the University of Muhammadiyah Malang carried out two socialization activities that focused on crucial issues in society, namely the dangers of online gambling and bullying. This socialization was held in two different locations: Dadaprejo Village and Al Firdaus Vocational School. The aim is to increase public and student awareness of the negative impacts caused by online gambling and bullying. Through interactive discussions and in-depth delivery of materials, this activity is expected to increase understanding, change mindsets, and encourage positive actions from all parties involved. With support from previous research, this socialization activity shows the importance of the role of education in reducing social risks faced by society and students.